Interactive Volume Reconstruction and Measurement on the Grid - Germain-Renaud, C.; Osorio, A.; Texier, R. (Methods of Information in Medicine, 2005)
Objectives: To prove the advantages of integrating grid computing within medical image analysis software, and to discuss the technological, sociological and health care-related issues.Methods: Presentation of an instant volume reconstruction and measurement tool (PTM3D) used in clinical practice, including percutaneous nephrolithotomy examples; description of a parallel implementation of volume reconstruction, evaluation of this implementation on lung and body reconstruction, presentation of the technical limitations for clinical use and description and discussion of a prototype grid implementation.Results: Volume reconstruction can broaden its medical scope and use by accessing high-performance computing systems; interactive exploration of medical images can co-exist with the usual batch workload of grid systems; the EGEE grid middleware offers some of the required core services; a fully adequate computing environment needs further evolution to integrate real-time constraints.Conclusions: Clinical experiments of a grid-enabled PTM3D become possible. Widespread adoption of grid technology in the medical images analysis field will benefit from this “early user” project. Convergences appear between two broadly different fields, high energy physics and medical image, towards the need of a smooth integration of the new resources offered by grid systems into the everyday tools of their respective end-users. It can be expected that the convergence will mature towards truly interactive grids, able to serve the needs of the medical community.
Keywords: Radiology; computing grids; visualization